Employing Polymer and Gel to Fabricate Scaffold-like Cancellous Orthopedic Screw: Polycaprolactone/Chitosan/Hydroxyapatite - AmirHossein Badami; Javad Esmaeili; Hasan Mirtalaie (Gels)
Using metallic/polymeric orthopedic screws causes cavities in bone trauma after the attachment of broken bones, which prolongs the healing. Yet, it remains unknown how to overcome such a challenge. The main aim of this research was to use both polymers and gels to fabricate and study a new PCL/chitosan/hydroxyapatite scaffold-like orthopedic screw for cancellous bone trauma. This screw, because of its low stiffness and its scaffold-based matrix (due to the gel part), can facilitate bone healing. Different concentrations of PCL (60–95% w/v) and chitosan (0–5% w/v) were blended according to the Response Surface Methodology using the Central Composite Design. The screws were fabricated using the freeze-drying technique. The screws were assessed mechanically, physically, and biologically (cell viability, cell attachment, DAPI, ALP staining, and Alizarin Red staining), and in vivo (a rat subcutaneous implantation model). Based on the results, screws depending on the PCL and gel content depicted different but notable mechanical behavior (10–60 MPa of compressive strength and 100–600 N force). The gel part could affect the physical properties of screws including water uptake (120%), degradation (18% after 21 days), porosities (23%), and mechanical strength (elastic modulus = 59.47 Mpa). The results also demonstrated no cytotoxicity towards MC3T3 cells (>80% cell viability) with good cell attachment, cell concentration, and mineralization (>90%) that was justified by the gel content. The results also showed good in vivo biocompatibility. To sum up, fabricated scaffold-like screws with gel content can be a good candidate for cancellous-bone-based orthopedic purposes. However, more in vitro and in vivo studies are required to optimize the PCL:gel ratio.